Mathematical Representation Ability of Senior High School Students: An Evaluation from Students’ Mathematical Disposition - Fitrianna, Aflich Yusnita; Dinia, Sofie; Mayasari, Mayasari; Nurhafifah, Astri Yuliani (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2018)
The purpose of this study is to describe studentsâ€™ ability in solving mathematical representation problems evaluated from mathematical disposition. Â The subjects are three students of 10th grade of public senior high school (PSHS) in Padalarang, West Java, Indonesia. They were selected from 35 students with high, medium, and low mathematical disposition ability. The results of the study showed that almost all of the students able to use visual representation to solve mathematical problems, and create mathematical models and solve problems by involving mathematical expressions. In contrast, most of students could not fulfill two indicators of the mathematical representation ability, i.e. creating the sketch of geometric patterns and making the mathematical model based on the situation and data given.